PEMAHAMAN KONSEP MATEMATIS MELALUI SCAFFOLDING EDUCATIONAL GAME EDUCAPLAY PADA MATERI OPERASI HITUNG BILANGAN - Rika Apriliana, Nuhyal Ulia (Integrative Perspectives of Social and Science Journal, 2025)
This research aims to determine the effect of scaffolding educational game educaplay on students' ability to understand mathematical concepts in class III mathematics subjects at SDN Purwosari 1. The method used in this research is the quantitative pre-experimental design method in the form of one group pretest posttest design. The instrument used in the research was a test question in the form of a description, where the researcher gave a pretest to students before being given treatment and a posttest after being given treatment. The population and sample in this study were all class III of SDN Purwosari 1, totaling 27 students. The results of the data analysis obtained show a significant effect, seen from the results of the paired sample t test with a sig value of <0.000. This shows that the sig value is <0.05. Thus Ho is rejected and Ha is accepted. So it is concluded that scaffolding educational game educaplay can influence the ability to understand mathematical concepts in mathematics subjects of class III students at SDN Purwosari 1.